2013
DOI: 10.1002/ar.22650
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of Chiropteran Shoulder Girdle in Flight

Abstract: New data on the mechanisms of movements of the shoulder girdle and humerus of bats are described; potential mobility is compared to the movements actually used in flight. The study was performed on the basis of morphological and functional analysis of anatomical specimens of 15 species, high speed and high definition filming of two species and X-ray survey of Rousettus aegyptiacus flight. Our observations indicate that any excursions of the shoulder girdle in bats have relatively small input in the wing amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…The scapula is highly important in bats due to its relationship with the wing‐beat cycle; the shoulder girdle movements resemble kinematics of a crank mechanism: the clavicle plays the role of crank, and the scapula plays the role of the connecting rod; also, the scapula is the site for attachment of important flight muscles (e.g., Mm. supraspinatus, infraspinatus, and subscapularis ) which control the dorsoventral movements of the forelimb (Panyutina, Korzun, & Kuznetsov, 2015; Panyutina, Kuznetsov, & Korzun, 2013; Vaughan, 1970a, 1970b). Although there are several descriptive, comparative, and morphofunctional studies about scapular girdles and forelimbs of bats (e.g., Altenbach & Hermanson, 1987; Hermanson & Altenbach, 1983, 1985; Miller, 1907; Norberg, 1970, 1972; Oxnard, 1968; Panyutina, Korzun, & Kuznetsov, 2011; Panyutina et al, 2013; Schliemann & Schlosser‐Sturm, 1999; Schlosser‐Sturm & Schliemann, 1995; Strickler, 1978; Swartz, Bishop, & Aguirre, 2006; Vaughan, 1959, 1966, 1970a, 1970b; Walton, 1969), studies on quantitative morphological variation of bat scapulae, using phylogenetic comparative methods, are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The scapula is highly important in bats due to its relationship with the wing‐beat cycle; the shoulder girdle movements resemble kinematics of a crank mechanism: the clavicle plays the role of crank, and the scapula plays the role of the connecting rod; also, the scapula is the site for attachment of important flight muscles (e.g., Mm. supraspinatus, infraspinatus, and subscapularis ) which control the dorsoventral movements of the forelimb (Panyutina, Korzun, & Kuznetsov, 2015; Panyutina, Kuznetsov, & Korzun, 2013; Vaughan, 1970a, 1970b). Although there are several descriptive, comparative, and morphofunctional studies about scapular girdles and forelimbs of bats (e.g., Altenbach & Hermanson, 1987; Hermanson & Altenbach, 1983, 1985; Miller, 1907; Norberg, 1970, 1972; Oxnard, 1968; Panyutina, Korzun, & Kuznetsov, 2011; Panyutina et al, 2013; Schliemann & Schlosser‐Sturm, 1999; Schlosser‐Sturm & Schliemann, 1995; Strickler, 1978; Swartz, Bishop, & Aguirre, 2006; Vaughan, 1959, 1966, 1970a, 1970b; Walton, 1969), studies on quantitative morphological variation of bat scapulae, using phylogenetic comparative methods, are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, wing strokes during the bat flight are produced mostly by movements of the humerus relative to the weakly mobile shoulder girdle. Note however, that the movements of humerus relative to shoulder girdle in flight employ only the caudal-most sector of available shoulder joint mobility (Panyutina et al 2013). …”
Section: Kinematics Of Chiropteran Wingmentioning
confidence: 98%
“…Our morphofunctional analysis of the bat flight apparatus based on dissections, manipulations on syndesmological preparations, and fluoroscopic research of flight has shown that a number of statements of the lock hypotheses are wrong and allowed the introduction of an alternative kinematic model of the bat shoulder girdle (Panyutina et al 2011(Panyutina et al , 2013. Below is its overview.…”
Section: Kinematics Of Chiropteran Wingmentioning
confidence: 98%
“…As exemplified by Rousettus aegyptiacus ( Fig. 5.5; Panyutina et al 2013), only the posterior most sector of available mobility in the shoulder joint is employed in flight, so that the elbow remains posterior to the dorsocaudal angle of the scapula throughout the wingbeat cycle. The elbow moves mainly dorsoventrally, but its way in the downstroke passes more anteriorly than in the upstroke; in the highest point it is raised well above the vertebral column, while the lowest point is at the level of the thorax mid-height.…”
Section: Morphofunctional Features Of Free Limbmentioning
confidence: 99%